Prevention and control of non-communicable diseases in antenatal, intrapartum, and postnatal care: a systematic scoping review of clinical practice guidelines since 2011 - Jenny Jung; Eshreena K. Karwal; Steve McDonald; Tari Turner; Doris Chou; Joshua P. Vogel (BMC Medicine, 2022)
Abstract Background Non-communicable diseases (NCDs) are a leading cause of maternal mortality and morbidity worldwide. The World Health Organization is developing new recommendations focusing on the management of NCDs for pregnant, intrapartum, and postnatal women. Thus, to support the development of new guidelines and recommendations, we aimed to determine the availability, focus, and scope of recommendations of current guidelines for the management of NCDs during pregnancy, intrapartum, and postnatal period. Methods PubMed, Global Index Medicus, TRIP, and Guideline International Network databases were searched on 31 May 2021, to identify any NCD-related guidelines published between 2011 and 2021 with no language or country restrictions. Websites of 165 professional organizations were also searched. Characteristics of included guidelines were analyzed, and recommendations were extracted from guidelines of five high-priority NCD conditions (diabetes, chronic hypertension, respiratory conditions, hemoglobinopathies and sickle cell disease, and mental and substance use disorders). Results From 6026 citations and 165 websites, 405 guidelines were included of which 132 (33%) were pregnancy-specific and 285 (88%) were developed in high-income countries. Among pregnancy-specific guidelines, the most common conditions for which recommendations were provided were gestational diabetes, circulatory diseases, thyroid disorders, and hypertensive disorders of pregnancy. For the five high-priority conditions, 47 guidelines were identified which provided 1834 recommendations, largely focused on antenatal care interventions (62%) such as early detection, screening tools, pharmacological treatment, and lifestyle education. Postnatal recommendations largely covered postnatal clinical assessments, lifestyle education, and breastfeeding. Health system recommendations largely covered multidisciplinary care teams and strengthening referral pathways. Conclusions This study provides a robust assessment of currently available guidelines and mapping of recommendations on NCD management within maternal health services, which will inform the scope of the World Health Organization’s future guideline development activities. This study identified a need to develop guidelines that consider NCDs holistically, with an integrated approach to antenatal, intrapartum, and postnatal care, and that are relevant for resource-limited contexts. Any such guidelines should consider what interventions are most essential to improving outcomes for women with NCDs and their newborns, and how variations in quality of NCD-related care can be addressed.